오일리스 부시용 고체윤활제 개발 - 공호성; 한흥구; 김진욱; 김경석; 박종식 (한국트라이볼로지학회, 2019)
This work aims to develop a dry lubricant for oilless bush, especially a solid lubricant, thereby creating a coating method with improved properties of anti-friction and load-carrying capacity without oil lubrication. In this work, spherical-shaped powders of thermosetting resin such as polyimide (PI) are mixed with a binder matrix obtained by mixing a fluorocarbon compound resin such as Polytetrafluoroethylene (PTFE) or Ethylene tetra fluoro ethylene (ETFE) with itself or with a non-fluorocarbon thermoplastic resin such as Polyether ether ketone (PEEK). And these dry lubricant mixtures are thickly coated (200-300 mm in the thickness) on the inner surface of the bush by using a wet-typed air-spray deposition method. It was found that the load-carrying capacity of the solid lubricant for excavator bush (60 mm in diameter) that operates under a high load condition (at 40 MPa) is greatly improved owing to the spherical-shaped powders of thermosetting resin. In addition, the coefficient of friction at the sliding surface is also reduced less than 0.1. Thick coating also lowers the contact stress at the edge of a bush that results in better tribological performances. The result suggests that the lubrication performance and durability life of the bush can be remarkably improved even without lubrication (oil or grease).